POTENTIAL DEVELOPMENT OF THE COMMUNITY LEADERS IN DIGITAL MEDIA SKILLS IN THE NEW NORMAL ERA - Boonnun, Vikrom; Aonkhong, Samit (Academic Journal Phranakhon Rajabhat University, 2021)
Potential development of the community leaders to maximize the effectiveness of digital media skills in the new normal era requires appropriate tool utilization in accordance with the characteristics and situations of data transmission, in addition to smart data analysis. For example, in the case of tool utilization efficiency for learning management, the users are required to possess technical knowledge and know-how in the use of digital tools, website resource tool usage, social tools, personal tools, and career development within the framework of positive criticism of data and information. Users are expected to possess expertise and appropriate implementation of digital tools through information usage, desirable for oneself and others in order to resolve social stigma caused by misinterpreting information leaning to publication which affected the community. Under the research assumptions, the development guidelines of digital media skills in the new normal era for community leaders consisted of 4 elements: questioning skills, discussion skills, technical skills, and objective specification skills. The presentation of this article led to suggestions on skill development curriculum for community leaders, expecting to the development of digital media skills in the new normal era so that they were capable to adapt themselves to current coronavirus (COVID-19) pandemic as well as potential emerging diseases in the future. The curriculum assumes that modern digital media skills were ready for responsive integration of communication among community members, both in terms of intellectual development and problem response.